Физическая геология: конспект лекций, читанных на Сибирских Высших женских курсах в 1913-1914 и 1914-1915 уч. гг. - Гудков П. П. Павел Павлович (Томск, Т-во "Печатня С. П. Яковлева", 1914)
Литограф. изд.